Enhancing learners' self-directed use of technology for language learning: the effectiveness of an online training platform. Issue 1 (2nd January 2016) - Lai, Chun; Shum, Mark; Tian, Yan
Abstract : Enhancing self-directed use of technology for language learning is essential for maximizing the potential of technology for language learning. Understanding how to construct learner training to promote this critical competency is of great significance. This study examined the effectiveness of an online training platform aimed at enhancing the willingness and necessary knowledge and skill set of learners to engage in self-directed use of technology for language learning through equipping them with the pedagogical rationales for self-directed technology use for learning, the strategic base for matching technology selection with learning goals and processes, and the tactics for using technological resources and tools effectively for language learning. A group of undergraduate students participated in the 12-week training. Analyses of students' survey responses prior to and after the training indicated that the training program was effective in inducing a greater frequency of self-directed use of technology for language learning and in promoting a greater willingness and stronger knowledge and skill base in support of such learning behaviors.